Mitigasi Bencana Alam di Kek Tanjung Lesung, Sudahkah Hyogo Framework for Action Diterapkan? - Natalia Yeti Puspita; Eko Widodo (Kosmik Hukum, 2021)
The threat of natural disasters in Indonesia can occur at any time and has caused suffering for humanity. The tourism industry also feels the impact and consequences of natural disasters. Tsunami on the coast of Banten at the end of 2018 has caused economic losses of up to hundreds of billions in the tourism sector. Mitigation of natural disasters, especially in the tourism industry, is still lacking the attention of the government. In the disaster management system, the state is the main actor who has full responsibility for dealing with the effects of natural disasters. The Government of Indonesia in 2005 ratified the 2005-2015 Hyogo Framework for Action as the government's guidelines in dealing with natural disasters, especially in the field of natural disaster mitigation. This study examines the implementation of HFA concerning natural disaster mitigation in the Special Economic Zone of Tanjung Lesung-Banten, and Cikadu Tourism Village Community. Socio-legal research is used as a research method and uses qualitative data analysis that is analytical descriptive and emphasizes primary data as the main data. This data was obtained by interview and observation. As for supporting primary data, library research is conducted. Based on the results of the study it can be seen that the Government of Indonesia has implemented the HFA by making Law No. 24 of 2007 concerning Disaster Management, but in practice law enforcement has not been felt by Banten coastal communities other than that there is no habit or cultural awareness of disaster response in the community.